MENTORING PEMBUATAN LAPORAN DANA KAMPANYE PILKADA SERENTAK - Gayatri, Gayatri; Sari W, N.L.; Lely A, N.K.; Yeni L, M. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Mentoring the finance report of election to the political parties is more important. Concurrent local election is an application of Law No. 1 of 2015 and Act No. 8 of 2015. The participants of the election candidates who filed by a political party, coalition of political parties or independent candidates qualified support. The Participants requires a large investment to achieve success. The Government requires participants to make the election campaign finance reports. The participant should create a special account for campaign funds. Campaign accounts used to accommodate the receipt and expenditure of the campaign. Acceptance of campaign funds could be money, services or goods. The participant must submit the finance reports in three stages: first, the start of the campaign finance reports. Reported the day before the campaign; secondly, the report campaign contributions; and third, reports the income and expenditure of campaign funds to be reported after the campaign is completed (final report). The final report submitted to the Local General Election Commission. The Local General Election Commission will appoint Public Accounting Firm to conduct an audit of campaign funds. The implementation is carried out by mentoring to all political parties, Kesbangpolinmasda Klungkung Regency, and General Election Klungkung Regency. Klungkung Regency selected because it will follow the election outright third phase in 2018 and the implementation phase has been started in 2017. The mentoring was done on August 11, 2015 by providing technical provisions for the preparation of election campaign finance reports.